Editoriales independientes en Chile: una política “literaria” del escritor-editor - Rafael Farías Becerra (IdeAs)
This article considers the possibility of conceiving the writer- publisher policy as another literary policy serving alternative literary politics. To this effect, the article examines the meaningful emergence of independent publishing houses in Chile, where the writer has taken over the role of publisher with the purpose of mobilizing his or her writing and his or her peers’ writing, as well as to create innovative aesthetic formats in which their works are presented. Thus, a politics of literary reception and the strategies of the writer seem to converge, the writer being considered as the producer of the conditions of existence and circulation of the works.